Analysis of difference-frequency wave loads and quadratic transfer functions on a restrained semi-submersible floating wind turbine - Li, Haoran; Bachynski-Polić, Erin E. (Ocean engineering, 2021)
One of the concerns regarding numerical simulation of floating wind turbines (FWTs) in waves is underprediction of resonant responses in the low-frequency range. In the present work, the difference-frequency wave loads on a restrained semi-submersible FWT subject to bichromatic waves are investigated by higher-fidelity tools (Computational Fluid Dynamics, CFD) and simplified engineering tools based on potential flow theory with Morison type drag. The effects of mean pitch angle (trim) and the wave force distribution on the multimember semisubmersible are assessed. Compared to the CFD results, wave loads estimated by engineering models are in good agreement at the wave frequencies, while slightly larger differences occur at the surge and pitch natural frequencies. The most significant underprediction of the surge force at the surge natural frequency occurs in the heave plate of the floater. Compared to the upright floater, the increased wave loads on the trimmed floater at the surge natural frequency are more significant than those at the pitch natural frequency. Furthermore, quadratic transfer functions (QTFs) are estimated based on the CFD model with a set of bichromatic wave cases. A new approach is found to use the CFD results to modify the QTFs in lower-fidelity engineering tools. This approach is validated against experimental measurements in irregular waves. Good agreement is achieved between measured and numerically estimated difference-frequency wave loads by engineering tools with modified QTFs. •Difference-frequency wave loads on a floating wind turbine via CFD, engineering model.•CFD predicts higher wave loads at higher wave frequencies.•The surge force increases for a trimmed floater. No significant change for pitch moment.•An approach to modify the potential flow QTFs based on CFD.•The modified QTFs reduce the underprediction of difference-frequency wave loads.